2018
DOI: 10.1002/tsm2.58
|View full text |Cite
|
Sign up to set email alerts
|

Poor agreement between ultrasound and inbuilt diffusion tensor MRI measures of biceps femoris long head fascicle length

Abstract: Objectives:This study aimed to determine whether diffusion tensor MR imaging (DTI) methodology inbuilt within manufacturer software can reliably measure biceps femoris long head (BFlh) fascicle length (FL) and to investigate agreement between ultrasound (US) measures and inbuilt DTI measures of BFlh FL. Methods: Both legs of 20 males were examined (40 legs). FL of the BFlh was determined utilizing two-dimensional ultrasound and diffusion tensor MRI assessment. Results: Reliability of DTI measures of BFlh FL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The reliability of measuring the fascicle length in hamstring muscles with DTI and tractography software was reported once 44 . These measurements were limited to the biceps femoris long head.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reliability of measuring the fascicle length in hamstring muscles with DTI and tractography software was reported once 44 . These measurements were limited to the biceps femoris long head.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of measuring the fascicle length in hamstring muscles with DTI and tractography software was reported once. 44 These measurements were limited to the biceps femoris long head. They reported good reliability and relative large MDC of 3.5 cm, using a simple and non-modifiable inbuilt manufacturer MRI tractography software.…”
Section: Compared To Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analyses and subgroup analyses results showed that the eccentric strength training, including NHE, did not show any large effect on the size of biceps femoris FL based on the studies that applied the MLE method and panoramic ultrasound scanning. Additionally, a previous study found a poor agreement between ultrasound assessments using a trigonometric equation method for estimating biceps femoris FL and diffusion tensor MRI measurements on the biceps femoris FL [ 61 ]. However, more comparisons between the existing ultrasound and MRI measurement techniques are needed to having an overall idea about the agreement level between MRI and ultrasound assessments of biceps femoris FL.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Franchi and colleagues 45 reported that this approach raises similar BF lh fascicle length estimation compared to extended-field-of-view imaging of the whole fascicle length. Yet, poor within-subject correlations between ultrasound and diffusion tensor MRI of BF lh fascicle length challenge these findings 65 , and it needs further investigations. Second, ultrasound measurements of muscle morphological and architectural characteristics were derived from limited locations of one selected muscle.…”
Section: Limitationsmentioning
confidence: 98%